1988
DOI: 10.1016/0304-3959(88)90180-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological functioning of children who have recurrent migraine

Abstract: Thirty-two children experiencing recurrent migraine, aged 8-17, were compared to 32 non-headache peer controls matched for age, sex, and social class. Each child completed an extensive battery of psychological tests, which consisted of (1) the Children's Depression Inventory (for children aged 8-13) or the Beck Depression Inventory (for children 14 and above), (2) the State-Trait Anxiety Inventory for Children (ages 8-12) or the State-Trait Anxiety Inventory, Form X (ages 13 and above), (3) the Children's Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
2
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 17 publications
9
79
2
1
Order By: Relevance
“…Similar results were reported by Anttila et al, who found that children with migraine had significantly higher scores of total, internalising and somatic symptoms than those without migraine [27]. The strong associations between migraine, depression and anxiety in children and adults demonstrated in some studies is partially confirmed by our findings of higher -but below threshold -scores in the anxious-depressed scale [9,10,12,16,38]. Egger et al studied a large population of children aged 9-15 years: girls who met DSM-III-R criteria for a depressive disorder had a four times higher prevalence of headaches than girls who were not depressed; girls with anxiety disorders had a three times higher prevalence of headaches than girls who were not anxious [39].…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were reported by Anttila et al, who found that children with migraine had significantly higher scores of total, internalising and somatic symptoms than those without migraine [27]. The strong associations between migraine, depression and anxiety in children and adults demonstrated in some studies is partially confirmed by our findings of higher -but below threshold -scores in the anxious-depressed scale [9,10,12,16,38]. Egger et al studied a large population of children aged 9-15 years: girls who met DSM-III-R criteria for a depressive disorder had a four times higher prevalence of headaches than girls who were not depressed; girls with anxiety disorders had a three times higher prevalence of headaches than girls who were not anxious [39].…”
Section: Discussionsupporting
confidence: 92%
“…Although increases in mean CDI scores have been reported in several other pediatric disorders such as migraine or diabetes mellitus (17)(18)(19), several factors may contribute to emotional symptoms in the specific disorder of epilepsy. These influences include CNS variables (e.g., effects of seizures, concomitant CNS conditions giving rise to seizures, and medications), as well as psychosocial factors (e.g., the stigma of having seizures) (20).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Bille 1 and Andrasik 10 have suggested that childhood migraine is also characterized by such features as depression, anxiety, poor adjustment, poor self-confidence, fearfulness, low motivation and endurance for physical activity and increased somatic complaints.…”
Section: Discussionmentioning
confidence: 99%